The Impact of Directed Reading Thinking Activity Strategy in Increasing Students’ Reading Motivation and Learning Achievement - Gia Arya Azzahara; Bachtiar Bachtiar; Ruminda Ruminda (Universitas Muhammadiyah Enrekang, 2024)
This study aims to explore the effectiveness of the Directed Reading Thinking Activity (DRTA) strategy in enhancing students' reading motivation and learning outcomes. Conducted using a mixed-methods approach, it involved 27 ninth-grade students at the Al-Gazali Islamic Boarding School. The study meticulously examines how the DRTA strategy, which encourages students to make predictions, pose questions, and enhance their comprehension through engaged reading, impacts their motivation to read and their levels of reading comprehension. By integrating both quantitative and qualitative research methods, this study provides a comprehensive analysis of students' reading performance before and after the implementation of the DRTA strategy. The findings indicate a significant improvement in students' reading motivation and overall reading achievement. This suggests the potential of the DRTA strategy as an effective pedagogical tool for comprehensive reading enhancement. This research offers insights into reading strategies that can foster a more engaging and productive reading environment for students, including those in Islamic boarding school settings.